Karakteristik Performansi Alat Pengering Indirect Passive Solar Drayer untuk Pembuatan Simplisia Biofarmaka - Fakhrina Fahma; Ilham Priadythama; Fatma Fitriana Sakina (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
The experiment has a purpose to observe performance of indirect passive solar dryer, so that it can raise the effectivity of drying process without decreasing the nutrition of biopharmaca rhizome. This observation using a fresh turmeric rhizome as an experiment matter. Each process using 2 kg turmeric rhizome. Turmeric rhizome cut alongside for about 3-5 mm. The design of this experiment using a factorial design with two influential factors which is can be control, that is the size of inlet hole and exhaust. Response of this experiment show by moisturising level from turmeric rhizome. The measuring of moisturizing level in each treatment are doing every 8 hours. The sample of turmeric rhizome are take for 3 sample. The trial result show that the temperature of dryer equipment is reached for 53.5 celcius. Moreover, the rate air flow for about 1,02 m/s in inlet hole and 0,43 m/s in exhaust hole. There are significant difference between inlet and exhaust level, moreover there is an interaction between inlet and exhaust hole to decline moisturizing level of simplisia turmeric. The optimal setting of this dryer equipment can be obtain with some action of closing the inlet hole for about ¾ and exhaust hole for about 1/2 from its part. The position of the rack didn’t influence the rate of decrease water content.